Moderate Consumption of Beer (with and without Ethanol) and Menopausal Symptoms: Results from a Parallel Clinical Trial in Postmenopausal Women - Trius-Soler, Marta (Nutrients, 2021)
The menopausal transition can be a challenging period for women’s health and a trigger of uncomfortable symptoms. Beer is the main food source of isoxanthohumol, a precursor of 8-prenylnaringenin, the strongest phytoestrogen identified to date. As phytoestrogens are reported to reduce perimenopausal symptoms, we evaluated if a daily moderate consumption of beer with (AB) and without alcohol (NAB) could improve menopausal symptoms and modify cardiovascular risk factors. A total of 37 postmenopausal women were enrolled in a parallel controlled intervention trial and assigned to three study groups: 16 were administered AB (330 mL/day), 7 NAB (660 mL/day), and 14 were in the control group. After a 6-month follow-up of the 34 participants who finished the trial, both interventions (AB and NAB) significantly reduced the severity of the menopause-related symptoms (p-value AB vs. Control: 0.009; p-value NAB vs. Control: 0.033). Moreover, AB had a beneficial net effect on psychological menopausal discomforts compared to the control group. As the sex hormone profile did not differ significantly between the study groups, the effects of both types of beers (AB and NAB) are attributed to the non-alcoholic fraction of beer. Furthermore, moderate NAB consumption improved the lipid profile and decreased blood pressure in postmenopausal women.